Kajian Pustaka: Peran Guru PAUD dalam Menstimulasi Perkembangan Motorik Anak Melalui Kegiatan Rutin Harian - Trifena Ruth Clara (Advances In Education Journal, 2025)
Motor development is a crucial aspect of early childhood growth that must be systematically stimulated through daily routine activities. This study aims to systematically review the role of early childhood teachers in stimulating children's motor development through daily routines. A Systematic Literature Review (SLR) was conducted, analyzing 18 relevant national journal articles published between 2015 and 2024. The findings reveal that early childhood teachers play a central role as facilitators in designing routine activities such as morning exercises, tidying up toys, handwashing, and mealtime, which serve as effective media for stimulating both fine and gross motor skills. Creative and educational integration of these routines has been shown to enhance children’s coordination skills and independence. However, challenges such as limited resources, high teacher–child ratios, and inadequate professional training hinder optimal implementation. This review highlights the urgency of strengthening teacher competencies in designing developmentally appropriate routine-based motor activities in early childhood education.